PERANCANGAN DESTINATION BRANDING SEBAGAI MEDIA PROMOSI DESA WISATA - Syaharani Putri, Fitri; Azharyandi Siswanto, Riky; Apsari, Diani (Telkom University, 2024)
Bandung is an Indonesian city located in the province of West Java. The city isone of the important centers on the island of Java which is famous for its various aspectsof culture, education, and tourism. Bandung is a city that has a variety of tourism, such asnature tourism, arts, culinary and many more. Not only in the city center, the regency areaalso has tours that are no less interesting. One of the potential natural attractions andcultural arts in Bandung Regency is located in Cibiru Wetan Village. However, Cibiru WetanTourism Village does not yet have Destination Branding and promotional media that are consistent and strong enough. This research is a research using mixed methods. The datacollection process was carried out by means of observation, questionnaires, interviews andalso literature studies. The analysis method used is SWOT analysis method and visual dataanalysis. The results of the design are instructions for using a visual identity onpromotional media that can show the unique values possessed by the Cibiru Wetan touristvillage. This research aims to design Destination Branding for Cibiru Wetan TourismVillage and its application on promotional media. The results of this research are expected to help the development of promotion and branding of Cibiru Wetan Village. So that it canincrease awareness and also tourists who visit. The study of thissubject is very useful forunderstanding how to use visual identity properly and correctly so that it becomes aconsistent identity, and is expected to be a solution to existing problems. Keywords: destination branding, Tourism Village, promotional media